MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN AUDITORY, INTELLECTUALLY, REPETITION (AIR) PADA MATERI HIDROLISIS GARAM DI KELAS XI IPA 2 SMA PGRI 6 BANJARMASIN - Ahmad Fauji; Atiek Winarti (Universitas Lambung Mangkurat, 2015)
Abstract. A research on the application of Auditory, Intellectually, Repetition (AIR) learning models in the hydrolysis of the salt material in class XI science 2 SMA PGRI 6 Banjarmasin. This study aims to determine: (1) improving the quality of teacher learning, (2) improvement of student learning activities, (3) student’s critical thinking skills, (4) improving student learning outcomes. This study uses classroom action research design with 2 cycles. Each cycle consists of planning, action, observation and evaluation, as well as analysis and reflection. The subject were student of class XI Science SMA PGRI 6 Banjarmasin with the number 28. The data include observation of teacher activity and student activity. Outcomes data of critical thinking skills collected using essay tests at the end of each lesson and learning outcomes data were collected using the test results to learn at the end of each cycle. Results of the study showed that the application of AIR learning models can improve teacher learning with good criteria in the first cycle to be very good in the second cycle. Student activity increased with good criteria in the first cycle to be very good in the second cycle. Student’s critical thinking skills increased each indicator by category quite well in the first cycle to be good on the second cycle. Application of AIR learning models can improve student’s mastery of learning outcomes of the average 69.35 % in the first cycle to be 89.30% in the second cycle or an increase of 19.95%.Keywords : auditory, intellectually, repetition (air) learning model, critical thinking skills, learning outcomes,hydrolysis of salts